Nonlinear Tolerancing: Variation Simulation and Assembly Analysis with Regard to Contact Interaction of Parts - Sergey Lupuleac; Margarita Petukhova; Julia Shinder; Maria Titova; Nadezhda Zaitseva; Maria Churilova (Axioms, 2024)
The variation analysis is a key tool for ensuring the high quality assembly in the process of developing the technology for manufacturing of aircraft parts. One of the main factors in variations is the deviations in the positioning procedure. This paper is devoted to the development of an approach that allows taking into account the variations during positioning and merging it with the special algorithm of contact problem solving. The impact of varied boundary conditions is incorporated into an additional vector of forces that can be interpreted as reactions to the shift of supports. The obtained results are illustrated with a case of wing-to-fuselage assembly.